Broken throne : a Red Queen collection - Aveyard, Victoria (New York : HarperTeen, an imprint of HarperCollins Publishiers, 2019)
An unseated king searches for meaning in a world altered by war. Enemy brothers clash one final time. A doomed queen pens words of hope to her future son. A Silver princess trusts a Red captain with her life in the chaos of an unknown land. A young Scarlet guard captain finds a glimmer of hope which will light a rebellion. And a hero whose spark started a revolution discovers where she belongs in peace. Delve into the dark and dangerous world of Red Queen with this companion, which includes three brand-new short stories as well as extra scenes, maps, family trees, flags, and much more.
Queen song -- Steel scars -- World behind -- Iron heart -- Fire light.
Keywords: Nobility -- Fiction; Government, Resistance to -- Fiction; Imaginary wars and battles -- Fiction; Nobility -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Young adult fiction; Nobility -- Fiction; Government, Resistance to -- Fiction; Fantasy; Short stories, American; Young adult fiction